A systematic review of the physical activity assessment tools used in primary care. (21st February 2017) - Smith, Toby O; McKenna, Máire C; Salter, Charlotte; Hardeman, Wendy; Richardson, Kathryn; Hillsdon, Melvyn; Hughes, Carly A; Steel, Nicholas; Jones, Andy P
Abstract: Background: Primary care is an ideal setting for physical activity interventions to prevent and manage common long-term conditions. To identify those who can benefit from such interventions and to deliver tailored support, primary care professionals (e.g. GPs, practice nurses, physiotherapists, health care assistants) need reliable and valid tools to assess physical activity. However, there is uncertainty about the best-performing tool. Objective: To identify the tools used in the literature to assess the physical activity in primary care and describe their psychometric properties. Method: A systematic review of published and unpublished literature was undertaken up to 1 December 2016). Papers detailing physical activity measures, tools or approaches used in primary care consultations were included. A synthesis of the frequency and context of their use, and their psychometric properties, was undertaken. Studies were appraised using the Downs and Black critical appraisal tool and the COnsensus-based Standards for the selection of health Measurement Instruments (COSMIN) initiative checklist. Results: Fourteen papers reported 10 physical activity assessment tools. The General Practice Physical Activity Questionnaire (GPPAQ) was most frequently reported. None of the assessment tools identified showed high reliability and validity. Intra-rater reliability ranged from kappa: 0.53 [Brief Physical Activity Assessment Tool (BPAAT)] to 0.67 (GPPAQ). Criterion validity ranged from Pearson's rho: 0.26 (GPPAQ) to 0.52 (Physical Activity Vital Sign). Concurrent validity ranged from kappa: 0.24 (GPPAQ) to 0.64 (BPAAT). Conclusion: The evidence base about physical activity assessment in primary care is insufficient to inform current practice.